Studi Netnografi Konten Ruqyah Syar’iyah Pada Akun Youtube Ustadz Muhammad Faizar - Unik Hanifah Salsabila; Adinda Dika Insani; Ramadhani Tri Astuti; Nenchi Nenchi; Vika Meila Sintia (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
Muhammad Faizar is a famous ustadz for his preaching using the Shar'iyah ruqiyah method. Ustadz Muhammad Faizar actively preached through his YouTube Channel through ruqiyah medicine. The purpose of this study is to understand public interaction on social media, especially on the YouTube platform through the account of Ustadz Muhammad Faizar. This research uses qualitative methods with a netnographic approach whose focus of observation is the YouTube social media approach. The object of this research is content in the form of ruqiyah impressions on the YouTube channel "Ustadz Muhammad Faizar". The results of this study show that of all the content of Ustad Muhammad Faizar da'wah videos on YouTube from 2020 the theme of ruqiyah syar'iyah. The content that netizens like the most is Qur'anic verse therapy for healing from magic. These findings are a requirement that digital media is one of the potential means for Islamic da'wah.